1972
DOI: 10.2134/agronj1972.00021962006400010001x
|View full text |Cite
|
Sign up to set email alerts
|

Double Cropping Following Winter Barley Harvest in Eastern Virginia1

Abstract: Soybeans (Glycine max L.) for grain and sorghum (Sorghum vulgare L.) and maize (Zea mays L.) for both grain and silage were planted in late June and in July following winter barley (Hordeum vulgate L.) to evaluate these crops in a double cropping system in eastern Virginia. Soybeans have been widely grown after barley in that area. Production and harvest costs were estimated and net returns were calculated from these estimates and the values of the crops produced. Grain yields were obtained over a 2‐year perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Production of small grains also generally improves farm cash flow due to summer harvest and grain sales. Yield of doublecrop soybeans ( Glycine max L.) planted following barley are also generally higher than when following wheat ( Triticum aestivum L.) because of earlier planting (Camper et al, 1972).…”
mentioning
confidence: 99%
“…Production of small grains also generally improves farm cash flow due to summer harvest and grain sales. Yield of doublecrop soybeans ( Glycine max L.) planted following barley are also generally higher than when following wheat ( Triticum aestivum L.) because of earlier planting (Camper et al, 1972).…”
mentioning
confidence: 99%
“…Lewis and Phillips (1976) noted a 40% yield reduction of corn double‐cropped with wheat compared with when corn was planted within the traditional window of 9 April and 12 May. Camper, Genter, and Loope (1972) noted greater net returns from double‐cropped corn following barley ( Hordeum vulgare L.) compared with double‐cropping barley with grain sorghum or soybean. They also found that summer crops could be planted about 2 wk earlier when following barley rather than following wheat in a double‐cropping system.…”
Section: Introductionmentioning
confidence: 99%
“…It is early maturing and short in stature with good winter hardiness, good straw strength, and high grain volume weight. Winter barley is an integral component of double‐cropping systems in the eastern United States due to its early maturity in comparison to wheat ( Triticum aestivum L.) (Browning, 2011; Camper et al, 1972). Both wheat and barley allow producers to extend the time available for planting and harvesting these crops and reduce the buildup of crop‐specific pathogens.…”
mentioning
confidence: 99%